Thermoelectric Properties of Arsenic Triphosphide (AsP3) Monolayer: A First-Principles Study - Fan, Liangshuang; Yang, Hengyu; Xie, Guofeng (Frontiers in Mechanical Engineering, 2021)
Recently, monolayer of triphosphides (e.g. InP3, SnP3, and GaP3) attract much attention due to their good thermoelectric performance. Herein, we predict a novel triphosphide monolayer AsP3 and comprehensively investigate its thermoelectric properties by combining first-principles calculations and semiclassical Boltzmann transport theory. The results show that AsP3 monolayer has an ultra-low thermal conductivity of 0.36 and 0.55 WmK-1 at room temperature along the armchair and zigzag direction. Surprisingly, its maximum Seebeck coefficient in the p-type doping reaches 2860 VK-1. Combining with its transport coefficients, the maximum ZT of p-type can reach 3.36 at 500 K along the armchair direction, which is much higher than that of corresponding bulk AsP3 at the same temperature. Our work indicates that the AsP3 monolayer is the promising candidate in TE applications, and will also stimulate experimental scientists' interest in the preparation, characterization, and thermoelectric performance tuning.